2005
DOI: 10.1051/vetres:2004053
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective genome analysis of a live vaccine strain of bovine viral diarrhea virus

Abstract: -A live bovine viral diarrhea (BVDV) vaccine, marketed as a derivate of the Oregon C24V strain, was used between the end of the 1960s and the beginning of the 1990s in Central Europe. Since laboratory investigations of mucosal disease cases in vaccinated animals suggested recombinations between the vaccine and wild type variants of BVDV, and recombinational nucleotide sequences seemed distinct from BVDV Oregon C24V, the aim of the present retrospective study was to analyze the genomes of pre-registration (term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…These cases occurred after vaccination with a live attenuated vaccine, termed here for ethical reasons BVDV-X [22]. The NS2-3 genes of the vaccine virus and of the MD isolates were found to be identical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cases occurred after vaccination with a live attenuated vaccine, termed here for ethical reasons BVDV-X [22]. The NS2-3 genes of the vaccine virus and of the MD isolates were found to be identical.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research activity was focused on BVDV-X. The complete nucleotide sequence of the marketed vaccine virus BVDV-X was determined, and sequence analysis did not reveal further genetic changes contributing to the cytopathogenicity of BVDV-X [24]. Furthermore, expression studies revealed that the insertion induces NS2-3 cleavage [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, four yaks from two counties were infected with BVDV-1b strains that were closely related to sequences from a BVDV vaccine Vedevac, with strong support in both the 5′UTR and N pro phylogenies. Vedevac was found as the main virus strain in batches of BVDV vaccine Oregon C24V in Hungary, and it was likely to have been picked up accidently during passages of the original Oregon C24V for vaccine development between the 1960s and 1990s [33]. In China, the Oregon C24V vaccine has been distributed to different laboratories as a reference strain for BVDV, but it has never been used for vaccination against BVDV in yaks in this region.…”
Section: Resultsmentioning
confidence: 99%
“…2) which we found in bovine cells prepared in Kenya with local serum [10]. Thus, it would come as no surprise if many laboratories working with cell cultures of ruminants unwittingly propagate pestiviruses (see, e.g., [4, 7, 62, 96], and unpublished observation). The taxonomy of pestiviruses is constantly changing, partly because of the discovery of new pestiviruses, but also because the criteria for the allocation of species status and division in subgroups within a given species (Fig.…”
Section: Bvdv: a Pestivirus Of The Flaviviridae Familymentioning
confidence: 91%